Agency-Clientele Relations: A Study of the Federal Communications Commission - William P. McLauchlan (Washington University Law Quarterly, 1977)
This Article will examine the recent court-mandated procedural changes of one regulatory agency-the Federal Communications Commission (FCC). Using empirical data, the Article will study the effect of the FCC’s efforts to remedy complaints about its processes on its operation.
Keywords: United States – Federal Communications Commission